Research and analysis of wireless power transfer technology based on sustainable energy - Erel, Mehmet Zahid (Afyon Kocatepe Üniversitesi)
Wireless power transfer (WPT) has been a topic of interest, especially in sustainable energy-based applications in recent years. The reason for this is the increase in the demand for energy originating from both social and political issues. Providing robust and flexible solutions without the need for wires, WPT technology in sustainable energy applications are thoroughly examined in this paper. The applications are categorized into two types as solar energy and wind energy. Herein, the inductive and microwave wireless charging technologies become prominent among other wireless charging technologies. The merits and demerits of WPT technology in sustainable energy applications are also evaluated in this paper. Besides, the design and analysis of inductive power transfer as promising technology are presented in solar energy applications. This paper is also expected to shed light on researchers who are interested in WPT technology based on sustainable energy.

Kablosuz güç aktarımı (WPT), özellikle son yıllarda sürdürülebilir enerji tabanlı uygulamalarda ilgi çeken bir konu olmuştur. Bunun nedeni hem sosyal hem de politik nedenlerden kaynaklanan enerji talebindeki artıştır. Kablolara ihtiyaç duymadan sağlam ve esnek çözümler sunan WPT teknolojisi, bu makale kapsamında sürdürülebilir enerji uygulamalarında kapsamlı bir şekilde incelenmektedir. Uygulamalar güneş enerjisi ve rüzgâr enerjisi olmak üzere ikiye ayrılmaktadır. Burada, diğer kablosuz şarj teknolojileri arasında endüktif ve mikrodalga kablosuz şarj teknolojileri öne çıkmaktadır. WPT teknolojisinin sürdürülebilir enerji uygulamalarında yararları ve zararları da bu makalede değerlendirilmektedir. Ayrıca, güneş enerjisi uygulamalarında gelecek vaat eden bir teknoloji olarak endüktif güç transferinin tasarımı ve analizi sunulmaktadır. Bu makalenin aynı zamanda sürdürülebilir enerjiye dayalı WPT teknolojisi ile ilgilenen araştırmacılara ışık tutması beklenmektedir.
Sürdürülebilir enerjiye dayalı kablosuz güç transferi teknolojisinin araştırma ve analizi
Keywords: Wireless Power Transfer; Inductive Power Transfer; Solar Energy; Wind Energy; Kablosuz Güç Transferi; Endüktif Güç Transferi; Güneş Enerjisi; Rüzgar Enerjisi